TINGKAT PENGETAHUAN MASYARAKAT TENTANG TSUNAMI SAFE ZONE DI JALAN DPR KOTA PADANG - Fregy Fregy Pratama; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The purpose of this study was to obtain information on the level of public knowledge about the tsunami safe zone on Jalan DPR Kota Padang, and the factors that influence public knowledge about the tsunami safe zone on Jalan DPR Kota Padang. This research uses descriptive quantitative method. The population in this study were all residents who were on Jalan DPR, in determining the sample using accidental sampling, namely determining the sample by chance who met directly with researchers in the field. And how to determine the number of samples using the Slovin formula, namely n = N / (1 + Ne2) with an error tolerance limit of 10% so 100 respondents were obtained. Data collection techniques using a questionnaire or a questionnaire in the form of tests. Based on the results of the study, it was found: 1) Public knowledge about the tsunami safe zone at Jalan DPR Padang City from 100 community respondents who had knowledge of the tsunami safe zone with a high category of 79%, 17% moderate and 4% low. 2) factors that influence people's knowledge, namely internal (age, education and experience) and external factors (information, environmental and socio-cultural).